Immunotherapy in the Treatment of Metastatic Melanoma: Current Knowledge and Future Directions - Massimo Ralli; Andrea Botticelli; Irene Claudia Visconti; Diletta Angeletti; Marco Fiore; Paolo Marchetti; Alessandro Lambiase; Marco de Vincentiis; Antonio Greco (Journal of Immunology Research)
Melanoma is one of the most immunologic malignancies based on its higher prevalence in immune-compromised patients, the evidence of brisk lymphocytic infiltrates in both primary tumors and metastases, the documented recognition of melanoma antigens by tumor-infiltrating T lymphocytes and, most important, evidence that melanoma responds to immunotherapy. The use of immunotherapy in the treatment of metastatic melanoma is a relatively late discovery for this malignancy. Recent studies have shown a significantly higher success rate with combination of immunotherapy and chemotherapy, radiotherapy, or targeted molecular therapy. Immunotherapy is associated to a panel of dysimmune toxicities called immune-related adverse events that can affect one or more organs and may limit its use. Future directions in the treatment of metastatic melanoma include immunotherapy with anti-PD1 antibodies or targeted therapy with BRAF and MEK inhibitors.